PERBANDINGAN KINERJA KEUANGAN BANK UMUM SYARIAH DAN BANK UMUM KONVENSIONAL - Irma Citrayani; Deddy Syaputra (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
The objective of this research is to make a comparison of the finance performance between Islamic Commercial Banks and Conventional Commercial Banks in Indonesia in the period 2013-2017 by using financial ratios. Financial ratios are used consisting of FDR/ LDR, ROA, CAR, BOPO and NOM/NIM. The data used in this research was obtained from the Financial Statements of Commercial Banks in 2013 to 2017, published by each Bank concerned. The sample in this research are 5 (five) Islamic Commercial Banks (Muamalat, Bank Syariah Mandiri, BNI Syariah, BCA Syariah dan BRI Syariah.), and 5 (five) Conventional Commercial Banks (BCA, BRI, BNI, Mandiri, dan Panin). Analytical techniques is used to see the comparison of financial performance of Islamic Commercial Banks with Conventional Commercial Bank. The analysis ratio also used by operating Microsoft Office Excel 2007, The analysis statistic descriptive and analysis of independent sample t-test is used by operating software SPSS 24. The analysis result showed that there are significant differences for each financial ratio between Islamic Commercial Banks and Conventional Commercial Banks in Indonesia. Islamic Commercial Banks has better performance in terms of FDR/ LDR ratio, while the Conventional Commercial Banks better performance in terms of the ROA, CAR, NOM/ NIM, and BOPO ratios.